Quality in the service of the hotel reception department of Hermosillo, Sonora, México - Ruíz Iduma, Sara (Universidad de Sonora, 2017)
The research studies the occupational profiles of the tourism sector in Hermosillo, Sonora, specifically analyzes the competencies of the receptionist of the top ten hotels in the city, with the purpose of determining the quality of the service based on behavioral and technical attitudes in their performance, such as the quality standards, the verbal and non-verbal communication that the receptionist projects, handling of complaints, assignment of rooms and departure of the guest. The methodology used is based on two instruments, a questionnaire and work experiences of one of the authors. The findings have concluded an efficient management of competencies regarding the quality of customer service.